Detection Gene of Luteinizing Hormone Receptor (rLH) in Madrasin Cattle using Polymerase Chain Reaction - Prasetyo, Ivo Febrina; Utomo, Budi; Madyawati, Sri Pantja (Jurnal Medik Veteriner, 2021)
The aim of this study was to determine the profile of the Luteinizing Hormone Receptor (rLH) gene in Madrasin cross breed cattle. The sample of this study used blood samples from 3 breeds of cattle. There were Madrasin from Bangkalan City, Madura from Bangkalan City and Limousin from BET Cipelang Bogor. The sample criteria were used female cattle around 2,5 years old and ever partus (once). The genomic DNA was extracted for polymerase chain reaction (PCR), followed by sequencing with software BioEdit Vers. 8.0 to determine the sequence of nucleotide bases. The results of this study were that three samples detected fragments in the form of DNA with nucleotide base of 373 bp. The conclusion, gene rLH in Madrasin Cattle can detected using PCR.